Thermal characteristics of turbulent rib-grooved channel flows - Eiamsa-ard, Smith; Promvonge, Pongjet (My University, 2009)
Experimental work has been performed to examine the combined effects of rib-grooved turbulators on the turbulent forced convection heat transfer and friction characteristics in a rectangular duct under a uniform heat flux boundary condition. In the experiments, three types of rib-groove arrangements: rectangular-rib and triangular-groove (RR-TG), triangular-rib and rectangular-groove (TR-RG) and triangular-rib with triangular-groove (TR-TG), were examined. Measurements were carried out for the duct of one aspect ratio, AR = W/H = 20 and duct height, H = 9 mm with rib height, e = 3 mm at three pitch ratios, PR = P/e = 6.6, 10 and 13.3. Experiments were conducted for the Reynolds number range of 3000 to 10,000. Influences of rib-groove arrangements on the Nusselt number and friction factor have been discussed and compared with smooth duct results under similar test conditions. Isothermal friction factors were also taken and presented. The obtained results of the smooth duct are in good agreement with the previous studies found in the literature. Experimental results also show that the duct with RR-TG arrangement provides maximum heat transfer rate and friction factor than others. On the other hand, the thermal enhancement index obtained at constant pumping power reveals that the TR-TG provides the highest values for all pitch ratios studied. Finally, correlations for the heat transfer (Nu), friction factor (f) and the enhancement index (η) have been developed as a function of pitch ratio (PR) and Reynolds number (Re). © 2009 Elsevier Ltd. All rights reserved.
Keywords: Friction factor; Groove; Heat transfer enhancement; Rib; Turbulator; Turbulent flow